Frequency of Low Acceptance of Postpartum IUCD and its Contributing Factors among Women in Tertiary Care Hospital - Tahira Nasrin, Natasha Bushra, Uzma Zia (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Post-partum intra uterine device insertion is the trend to increase the importance of family planning services immediately after delivery, to enhance motivation and acceptance among women. It has additional advantage to provide best care in terms to escalate health of woman and increasing healthy timing and space among children Aim: To determine frequency of women accepting immediate PPIUCD insertion and frequency of contributing factors in those refusing insertion of PPIUCD. Methods: A Cross-sectional study, in setting of Gynaecology Services Hospital, Lahore/SIMS was carried out over a period of six months from 03-10-2019 to 02-04-2020.A total of 215 antenatal women, women admitted in labour room for delivery either vaginal (including vaginal birth after C/section) or caesarean delivery were included in this study. The women refusing insertion of PPIUCD were interviewed by using a predesigned questionnaire. Results: Mean age of the patients was 26.38±2.91 year. Majority of the patients 130(60.5%) delivered vaginally while in 85 patients (39.5%) caesarean section was carried out. Immediate PPIUCD insertion accepted by 71 patients (33%). Distribution of contributing factors in patients who refused insertion of PPIUCD as follows: Age 18-25 years, 56(38.9%), low educational status 103 (71.5%), misconception 93(64.6%), partner’s wish 33(22.9%), Primiparity 16(11.1%), fear of side effects 11(7.6%) and other contraceptive method 41(28.5%). Stratification with regard to age, parity and mode of delivery was carried out. Conclusion: Our study demonstrated frequency of women accepting immediate PPIUCD insertion 33%. Keywords: Post-partum IUCD, Low acceptance, Pregnant women